IDEOLOGI MASKULINITAS DALAM IKLAN MEN’S BIORE DOUBLE SCRUB: SEBUAH KAJIAN KRITIS - Lela Nurfarida (Universitas Sultan Ageng Tirtayasa, 2016)
Language present as a form of cultural development in a community. Language is able to demonstrate an existence or identity of a community. One that shows the development is a remarkable phenomenon in the language of commercial advertising at the moment. Advertisement becomes a complex and potential text. Behind its visual appearance and language, the advertisement carries a certain culture that need recognition. The cultural change that appears in the face cleanser advertisement is a product of mass culture that no longer choose absolute gender. This study aimed to describe the masculine representations and ideologies are implied in the ad Men's Biore Double Scrub based linguistic construction, discourse, and semiotics. This study focus on dimensions of language as a carrier of a message and the attribute in the context of society. Variations languages supported visual appearance of the man in face cleanser ads Men’s Double Scrub Biore wants to put the identity of a real man who accepted in society of postmodern era. Critical analysis of this advertisement will expose a new masculinity culture featured in a cleaners advertisment and bring changes in the current thinking of gender in the present era.